2011
DOI: 10.1007/s12303-011-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

K-Ar ages of the Quaternary basalts in the Jeongok area, the central part of Korean Peninsula

Abstract: The Quaternary basalts along the Chugaryeong Fault zone in central part of the Korean Peninsula are composed of two stratigraphic units in the Jeongok area, calling the Chatan and Jeongok basalts. K-Ar analyses of the mixture of the finegrained plagioclase and anorthoclase from the 18 basalt samples were carried out to reveal the volcanic activity of the area. The results show that the Chatan and Jeongok basalts give a uniform age, giving the weighted average ages of 0.15 ± 0.01 and 0.51 ± 0.01 Ma, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…9 with the previous K-Ar age data. The revised protocol successfully reproduces 40 Ar/ 39 Ar age results similar to the average K-Ar ages of 150 ± 10 Ka and 510 ± 10 Ka from Ryu et al (2011). In addition, other volcanic activity at ca.…”
Section: Application To Quaternary Basalt In the Jeongok Area Koreasupporting
confidence: 61%
See 1 more Smart Citation
“…9 with the previous K-Ar age data. The revised protocol successfully reproduces 40 Ar/ 39 Ar age results similar to the average K-Ar ages of 150 ± 10 Ka and 510 ± 10 Ka from Ryu et al (2011). In addition, other volcanic activity at ca.…”
Section: Application To Quaternary Basalt In the Jeongok Area Koreasupporting
confidence: 61%
“…In addition, the mantle source component of the Jeongok basalt is different from that of other Cenozoic basalt in Korea (Choi et al 2006). Ryu et al (2011) suggested that there were two major volcanic eruptions in this area, at ca. 150 and 510 Ka based on K-Ar ages.…”
Section: Application To Quaternary Basalt In the Jeongok Area Koreamentioning
confidence: 89%
“…However, the tectonic evolution responsible for formation of the Chugaryeong fault system remains unclear (e.g., Shibuya et al, 1985;Ryu et al, 2011). The crust of the Korean Peninsula presents typical characteristics of a continental crust.…”
Section: Tectonics and Seismicitymentioning
confidence: 99%
“…The NHRL in Figures 6d and 6e is Northern Hemisphere Reference Line (Hart, 1984). Sources for literature data: Quaternary ADK (adakitic high‐Sr andesites and dacites) in the Chugoku district (Feineman et al, 2013; Kimura, Gill, et al, 2014; Kimura et al, 2015; Pineda‐Velasco et al, 2015, 2018), Cenozoic basalts in East Asia (Basu et al, 1991; Brenna et al, 2014; Brenna, Cronin, Smith, Maas, et al, 2012; Brenna, Cronin, Smith, Sohn, et al, 2012; Chen et al, 2007, 2018; Choi et al, 2006, 2008, 2014; Choi & Kim, 2012; Choi & Kwon, 2005; Ho et al, 2003; Kuritani et al, 2009, 2011, 2013, 2017; Liu et al, 1994; Park et al, 2005; Ryu et al, 2011; Sakuyama et al, 2013; Sakuyama, Nagaoka, et al, 2014; Sakuyama, Nakai, et al, 2014; Song et al, 1990; Sun et al, 2014; Tatsumi et al, 2005; Tatsumoto & Nakamura, 1991; Wang et al, 2011; Xu et al, 2013; Zeng et al, 2013; Zhang et al, 1995, 2012, 2015; Zou, 1998; Zou et al, 2000, 2003), seafloor basalts from Pacific and Shikoku Basin (Pineda‐Velasco et al, 2018, references therein), sediments (Ben Othman et al, 1989; Chauvel et al, 2009; Cousens et al, 1994; Hauff et al, 2003; Hemming & McLennan, 2001; Ishikawa & Nakamura, 1994; Pearce et al, 1999; Plank et al, 2007; Shimoda et al, 1998; Terakado et al, 1988). ...…”
Section: Resultsmentioning
confidence: 99%